A Preliminary Assessment of the Impact of Plea Bargaining Among a Sample of Waiver-Eligible Offenders. (July 2015) - Burrow, John D.; Lowery, Patrick G.
This study examines the use of plea bargaining among a sample of waiver-eligible juveniles. Using focal concerns as our theoretical foundation, we examine whether concerns about public safety and blameworthiness help to shape plea bargain decision making. Data from a juvenile court in one South Carolina jurisdiction were analyzed using logistic regression ( N = 241). This research finds that several factors influence the plea bargain decision including type of offense, number of victims, age, and race. Additionally, the analysis shows that there are several interactive effects between race, first-time offenders, and presence of an attorney. The theoretical and policy implications of these findings are discussed.